Building background knowledge for academic achievement : research on what works in schools - Marzano, Robert J. (Gale virtual reference library., 2004)
Explains why insufficient background knowledge is a chronic cause of low achievement, and describes how a carefully structured combination of two approaches--sustained silent reading and instruction in subject-specific vocabulary--can help rescue low achievers and boost the academic performance of all students.